New species of Crotonia (Acari: Oribatida: Camisiidae) from Nothofagus and Eucalyptus forests in Victoria, Australia, with a redescription of the fossil species Crotonia ramus (Womersley, 1957) - Colloff, Matthew; Perdomo, Giselle (Zootaxa, 2009)
Six new species of oribatid mite belonging to the genus Crotonia are described from wet forests in Victoria, Australia. Crotonia alpina sp. nov., C. cornuta sp. nov. and C. victoriae sp. nov. belong to the Capistrata species-group, having the full complement of notogastral setae in the c series; whilst C. momitoi sp. nov., C. blacki sp. nov. and C. gadubanudi sp. nov. are members of the Cophinaria species-group, lacking setae c 2 . The fossil species Crotonia ramus (Womersley, 1957), also a member of the Cophinaria group, is redescribed from Tertiary Kauri pine resin (Agathis yallournensis). The new members of the Capistrata group share an unique combination of characters, including long flagelliform setae c 3 , shorter setiform c 2 and with setae c 3 the shortest of the c series; lateral strips of the notogastral shield ornamented with fields of tubercles; narrow, blunt bothridial auriculae and elongate parallel apophyses of setae h 2 projecting horizontally. The morphological homogeneity of this cluster of species is mirrored by the members of the Cophinaria species-group described herein which, together with C. pyemaireneri Colloff, 2009 and C. tasmanica Łochyńska, 2008 from Tasmania, plus C. jethurmerae Lee, 1985 from South Australia, share relatively well-developed setae d 2 , a porose notogastral shield with narrow lateral tuberculate strips; elongate, acute bothridial auriculae; long, flagelliform setae p 1 and relatively short apophyses of setae h 2 , divergent apically, and projecting posteriodorsally. The Victorian members of the Capistrata andCophinaria species-groups represent two homogeneous clusters of species associated with temperate rainforest refugia and wet sclerophyll forest in high-rainfall zones. An identification key is provided to the Australian species of Crotonia.